2019
DOI: 10.1002/nafm.10328
|View full text |Cite
|
Sign up to set email alerts
|

Fishery‐Scale Discard Mortality Rate Estimate for Haddock in the Gulf of Maine Recreational Fishery

Abstract: Empirical discard mortality rate estimates are vital to both stock assessments and fishery management, especially for stocks that experience high discard rates, such as in the recreational rod‐and‐reel fishery for Haddock Melanogrammus aeglefinus in the Gulf of Maine. The objective of the present study was to derive a fishery‐scale discard mortality rate estimate for Haddock that are captured and released in the Gulf of Maine recreational fishery by combining results of an electronic‐tagging telemetry experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…to the mortality of a species can be used to recommend best fishing practices within a given fishery. For example, previous research regarding best practices for gadoids in the recreational rod‐and‐reel fishery offered suggestions to avoid fishing grounds with smaller individuals (Capizzano et al 2019) and to minimize handling times (Capizzano et al 2016) so as to reduce injury and mortality. Interestingly, the current study found no significant predictors of AVM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to the mortality of a species can be used to recommend best fishing practices within a given fishery. For example, previous research regarding best practices for gadoids in the recreational rod‐and‐reel fishery offered suggestions to avoid fishing grounds with smaller individuals (Capizzano et al 2019) and to minimize handling times (Capizzano et al 2016) so as to reduce injury and mortality. Interestingly, the current study found no significant predictors of AVM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, soak time may not accurately reflect the amount of time individuals were confined in lobster traps, as fish have been observed to enter and exit trap gears at will (i.e., Jury et al 2001; Cole et al 2004). It is also important to consider the likelihood of additional stressors that were unaccounted for in our survival model (i.e., air exposure duration, fish size, and catch biomass) and that have been found to be related to mortality in other species (i.e., Capizzano et al 2016, 2019). Given these uncertainties, further research into the specific factors contributing to the mortality of Atlantic Cod captured in the GOM commercial lobster fishery is needed in order to provide recommendations for best fishing practices.…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent studies indicate that discard mortality rates in recreational fisheries are influenced by numerous biological, environmental, and technical factors (e.g., Capizzano et al, 2016Capizzano et al, , 2019Weltersbach et al, 2019). Therefore, fishery-or region-specific estimates of discard mortality and recommendations for anglers for best practices in catch and release of black sea bass are required to provide the information needed for stock assessments, fishery management, and conservation efforts.…”
Section: Fishery Bulletinmentioning
confidence: 99%
“…Step 2 included the application of a variance test on depth observations recorded at defined intervals throughout the detection history of each acoustically tagged fish (Capizzano et al, 2016(Capizzano et al, , 2019. Only intervals with at least observations were included in the analysis.…”
Section: Fate Assessmentmentioning
confidence: 99%
“…The behavior of these transmitters attached to known‐dead fish can then be scrutinized, and any similar patterns among fish released alive imply discard mortalities (Yergey et al 2012; Capizzano et al 2016; Zemeckis et al 2020). A more opportunistic approach to identifying fate involves resighting or recapturing a live, tagged animal after a period at large, thereby confirming that all data between release and recapture were generated by that individual and allowing for comparisons as above (i.e., a positive control; Capizzano et al 2019). Even with these approaches, comparing the detection information of individuals with known and unknown fates is typically at best a semi‐quantitative procedure (Benoît et al 2012).…”
mentioning
confidence: 93%